Analisis Gambaran Morfologi Limfadenitis Tuberkulosis Menggunakan Metode Biopsi Aspirasi Jarum Halus dan Polymerase Chain Reaction - Delyuzar; Soekimin; Dedy Suryadi (Perhimpunan Dokter Spesialis Patologi Indonesia (IAPI), 2020)
BackgroundIndonesia is the 2nd largest of tuberculous (TB) cases in the world. Therefore, TB must be controlled by increasing the capacity anddeveloping universal access needed for TB diagnose accurately and quickly. Progression in controlling TB and decreasing theconsequence can be accelerated through early detection and promt treatment. This study used PCR test as gold standard, albeitthe high cost. Thus, quick, accurate and low cost diagnostic method is needed. In this case morphologic features requirementinclude the existence of epithelioid and necrosis in FNAB smears. Objective was to analyze morphologic features of tuberculosislymphadenitis using FNAB and PCR methods.MethodsThis study is a cross sectional analysis. N samples are all kind of lymphadenitis tuberculosis. Morphologic features in FNABcytology must be confirmed using PCR test and performing chi-square test respectively.ResultsEpitheloid and necrosis features of TB lymphadenitis on FNAB showed 100% positive on PCR methods. This study divided intothree groups. Statistic analyses between group I and II, group II and III showed in significant differences (p=0.074); while betweengroup I and III showed significant differences (p<0.05).ConclusionsPCR method could confirmed morphologic features (epitheloid and necrosis) of TB lymphadenitis